The Impact of Corruption on FDI: An Application of Efficient Grease Hypothesis to EU Countries - Elif Kardesler; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2009)
This paper empirically examines the impact of corruption on FDI in European Union countries, including candidate countries. Our aim is to verify whether Efficient Grease Hypothesis does hold in the case of the EU. Contrary to the Hypothesis, we find that corruption has a negative impact on FDI.
Keywords: C31; D73; F21; 330; FDI; Corruption; Efficient Grease Hypothesis; OLS